1994
DOI: 10.1002/jrs.1250250720
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution stimulated Raman spectrum of ethane (12C2H6) in the region of the CH symmetric stretching

Abstract: The high-resolution (ca. 0.008 cm-') stimulated Raman spectrum of the strongly perturbed C-H symmetric stretching region of 12C2H, at room temperature and at a rotational temperature of ca. 30 K, achieved in a free supersonic jet expansion chamber, is reported. The spectrum is tentatively analysed and assigned in terms of a simplified vihratiow-torsiornotation Hamiltonian. Besides the already known strong Fermi resonance, several Coriolis torsional interactions are identified as the major perturbations in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…It, however, disagrees with the result of Lepard et al, 12 ϭ ϩ0.23 (18). The latter value, which was used in the recent literature (10,11), is different enough from the other one to significantly influence the present as well as our previous (21) vibrational assignments. Experimental evidence supports our choice.…”
Section: Discussioncontrasting
confidence: 82%
“…It, however, disagrees with the result of Lepard et al, 12 ϭ ϩ0.23 (18). The latter value, which was used in the recent literature (10,11), is different enough from the other one to significantly influence the present as well as our previous (21) vibrational assignments. Experimental evidence supports our choice.…”
Section: Discussioncontrasting
confidence: 82%
“…For C 2 H 4 , the conditions are apparently good. The occurrence of E bands of the b 2g CH 2 wagging mode and the a g CH 2 -scissor and CC-stretch modes is explained by s-wave and d-wave 18 For the free molecule, the IR and the Raman activity of a mode is indicated by "IR" or "R", respectively; p and s denote directions of the IR dipole parallel and perpendicular to the CC axis, respectively. "pol."…”
Section: Discussionmentioning
confidence: 99%
“…Torsions a 1u are inactive; see also ref . “FR” indicates the Fermi-resonance effect that gives two lines . For the free molecule, the IR and the Raman activity of a mode is indicated by “IR” or “R”, respectively; p and s denote directions of the IR dipole parallel and perpendicular to the CC axis, respectively.…”
Section: Adsorbate Spectramentioning
confidence: 99%
“…The greatest difference was localized in the vicinity of the ν 1 peak of methane and was about 4% relative to its height (see Figure S4). It was found that the extracted ethane bands (Fermi‐coupled cluster of the ν 1 , 2ν 2 , 2ν 6 , 2ν 8 , 2ν 11 , and 2ν 12 vibrations 71,72 ) were narrower compared with the spectrum of pure ethane at the same pressure (see Figure S4). We suppose that the collisional broadening effect for the rotational–vibrational lines of C 2 H 6 perturbed by CH 4 is less than the effect of C 2 H 6 –C 2 H 6 collisions.…”
Section: Resultsmentioning
confidence: 99%